On the Performance and Efficiency of Surface Air Cooler Working under High Temperature and High Humidity Condition. (28th September 2022) - Yang, Juan; Yu, Jing; Wang, Shijing; Yan, Weidong
Abstract : Surface air cooler is widely used in refrigeration, air conditioning, chemical dehumidification, and other related fields. Nowadays, the application of surface air cooler has been mature under standard working conditions, and more and more research has been carried out on its application. However, when conventional surface air coolers are directly used under high temperature and high humidity conditions (the temperature is higher than 30°C, both the humidity ratios are higher than 20 g/kg dry air), or under conditions with strict dehumidification requirements, the expected results are often not achieved. Therefore, taking the conventional surface cooler as an example, the performance and efficiency of dehumidification of the surface cooler under high temperature and high humidity are investigated specifically in this paper. Based on the above model and experiment, the influence of operation parameters on heat and mass transfer of surface air cooler is analyzed. At the same time, the change law of heat and mass transfer capacity, dehumidification performance, and heat transfer efficiency of a surface air cooler is specially investigated. Results proved that under high temperature and humidity conditions (34.8°C, 23.03 g/kg dry air), lower head-on wind velocity could realize deeper humidification effects effectively, while water velocity showed fewer impacts. As shown in the experiment, when water velocity increased to 1.2 m/s, and head-on wind velocity dropped to 1.06 m/s, the humidity ratio at the air outlet reduced to 8.88 g/kg while heat-transfer efficiency reached 0.778; however, when head-on velocity increased to 2.5 m/s and water velocity rose to 1.2 m/s, humidity ratio at air outlet dropped to 13.17 g/kg only, and heat-transfer efficiency reached merely 0.572. In conclusion, this paper has established an accurate and effective mathematical model for analyzing the heat transfer and dehumidification characteristics of the surface cooler under high temperature and high humidity conditions, which provides a reference for the development and design of dehumidification surface cooler under special conditions. More importantly, the conclusion of this paper also points out that, different from the adjusting strategy under conventional working conditions, reducing the head-on wind speed is the best adjusting strategy when the air surface cooler is used in high temperature and high humidity working conditions. This adjusting strategy is not only conducive to promoting the air to achieve a better dehumidification effect but also can effectively improve the efficiency of the surface cooler.